Developing aerobic and anaerobic fitness usiing small-sided soccer games: Methodological proposals. - Clemente, F. M.; Lourenco Martins, F. M.; Mendes, R. S. (Strength and Conditioning Journal, 2014)
Soccer coaches have been increasing the use of small-sided games in soccer training. These small-sided games show a similar efficiency as traditional running methods (without the use of a ball) in developing physical fitness in soccer players. Moreover, small-sided games enable the development of both technical skills and tactical actions. However, there is little knowledge about the proper organization that is necessary for small-sided games to achieve the desired effects in soccer players. This review aims to summarize the physiological effects on soccer players promoted by small-sided games and to develop a methodological schematization for organizing small-sided games.